Pengaruh Temuan Audit, Ketepatan Waktu Penyampaian Laporan Keuangan dan Kecukupan Pengungkapan Laporan Keuangan Terhadap Opini Audit Atas LKPD Provinsi/Kabupaten/Kota Sumatera Selatan - Annisa, Rahmi Nur; Sari, Kartika Rachma; Rosy Armaini (JAF (Journal of Accounting and Finance), 2024)
The purpose of this study is to examine the impact of audit findings, the timing of financial reporting, and the adequacy of financial disclosure on the audit opinion. This research focuses on the agency theory that connects the relationship between the agent, the head of the district, and the community as the principal. The study used a saturated sample of 54 samples comprising 1 province, 13 districts, and 4 cities in South Sumatra in the period 2020-2022. The method of analysis used is panel data regression. The estimated panel data model used is the Common Effect Model. The hypothesis test used is a T test to measure partial variable influence and a F test for measuring simultaneously the influence of variables. The results of this study showed partially that the audit findings have a negative influence on the audit opinion. The timing of the financial report does not affect the audit opinion, nor does the adequacy of financial report disclosure have any influence on the auditor's opinion. However, the audit findings, the exact timing for financial reporting, and the appropriateness of financial statement disclosures together have an impact on the auditing opinion.Keyword: Audit Opinion; Financial Report of Local Government.